Impact of carbon nanotubes in a vertical channel for Casson fluid with heat/mass flux: an analytical study - Hazarika, Silpi; Ahmed, Sahin (Journal of Naval Architecture and Marine Engineering, 2023)
In this article, unsteady MHD free convection ﬂow of Casson fluid with carbon nanotubes is investigated and the ﬂow is considered through a vertical channel and the single-wall carbon nanotubes (SWCNTs) and multiple-wall carbon nanotubes (MWCNTs) are placed within the channel with Engine oil as base ﬂuid. The problem is modelled and then solved analytically using perturbation technique. Graphical results are obtained through computational software Mathematica code 8.0 and elaborated for various embedded parameters. It is observed that Casson parameter and nanoparticle volume fraction accelerates the flow velocity for both cases of MWCNT and SWCNT. Throughout the discussion it is seen that, MWCNT is more dominant than the SWCNT for some key physical parameters. A validation of the present work is shown by comparing the current results with existing literature. Applications of this study arise in the field of nanotechnology, hard water, conductive plastics, air reﬁnement scheme, mechanical compound materials, superﬂuous strong ﬁlaments, sensors devices, storage of gas, bio-sensors and many more.